Investigation on the activation mechanisms of coal gangue and the corresponding CO2 mineralization potential - Zhu, Lei; Liu, Chengyong; Duan, Gang; Liu, Zhicheng; Shen, Lingling; Zhou, Yuejin; Fang, Kun (Frontiers in Materials, 2025)
Coal gangue can be used for CO2 mineralization and then be backfilled into the goaf, which can simultaneously address the long-term management of coal gangue and CO2. Mechanical and composite activation methods were employed to enhance the activity and mineralization potential of coal gangue, and ion leaching experiments were conducted to leach active ions from mechanically-activated coal gangue (MACG) and composite-activated coal gangue (CACG) in this study. Additionally, the evolution of the mineralization potential of MACG and CACG samples under different conditions was explored by inductively coupled plasma-optical emission spectrometry (ICP-OES) tests. The results show that with the extension of milling time, the leaching rates of Ca2+, Mg2+, and K+ of MACG samples gradually increase, while the leaching rate of Ca2+ of CACG samples gradually decrease, and leaching rates of Mg2+ and K+ of CACG samples gradually increase. The activation mechanism of MACG samples was analyzed by the dry powder laser particle size analysis (DPLPSA) and Brunauer-Emmett-Teller (BET). The results show that when the milling time is less than 2 h, the average particle size of MACG samples decreases significantly and the specific surface area increases significantly with the extension of the milling time. However, when the milling time increases to 4 h, the changes in particle size and specific surface area become less significant, leading to an increase in the non-uniformity coefficient and a reduction in porosity. Thermogravimetry (TG) analysis was used to analyze the material components of MACG and CACG samples. It was found that due to the combustion of organic matter, thermal activation after mechanical activation can effectively improve the activity of coal gangue. After mechanical activation, the activity improvement of coal gangue is gradually reduced due to the advance of the transition temperature from metakaolinite to mullite. Finally, MACG and CACG samples before and after mineralization were analyzed by TG tests. The mineralization capacity of MACG samples with a 2-hour milling time was found to be 0.43%, whereas CACG samples achieved a higher mineralization rate of 0.53%.